Experiences of Military Spouses of Veterans With Combat‐Related Posttraumatic Stress Disorder. Issue 6 (12th August 2016) - Yambo, Teresa W.; Johnson, Mary E.; Delaney, Kathleen R.; Hamilton, Rebekah; Miller, Arlene Michaels; York, Janet A.
Abstract: Purpose: To explore the experiences of military spouses living with veterans with combat‐related posttraumatic stress disorder (PTSD). Design: Husserlian phenomenology was chosen as the theoretical framework because it allowed a deeper understanding of the unfolding of the spouses' daily experience. Methods: A purposive sample of 14 spouses living with veterans with symptoms of PTSD participated in unstructured interviews. Data were analyzed using a modification of the Colaizzi phenomenological method. Findings: Spouses recognized that the veteran was no longer the same person, with life becoming one of living with the unpredictability of PTSD. The spouses bore the burden to maintain normalcy in the family and eventually created a new life. Conclusions: Military spouses endure psychological stress and strain, while living with a veteran with PTSD. There is a need for more programs to support the resilience of military spouses. Clinical Relevance: Life for military spouses of veterans with PTSD is ever‐changing and unpredictable. Practitioners need to be aware of the stress that spouses experience and develop programs and interventions that bolster the resilience of military families.